Analisis Profitabilitas Strategis PT Unilever Indonesia Tbk Tahun 2021–2023: Evaluasi Kinerja dan Implikasi Strategi Bisnis - Resya Rahmatu Nissa; Siti Afifaful; Syifa Nur Aulia; Saprudin Saprudin; Robbiansa Robbiansa; Ryan Akbar Maulana; Fitri Fallah Prambudini; Cahya Wahyu Kusumaningsih; Rois Kurniawan; Sarnih Safitri (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2025)
This study aims to analyze the strategic profitability of PT Unilever Indonesia Tbk during the period 2021–2023. Using a descriptive quantitative approach, this study evaluates the company's financial performance through profitability ratio analysis, including Gross Profit Margin (GPM), Operating Profit Margin (OPM), Net Profit Margin (NPM), Return on Assets (ROA), and Return on Equity (ROE). Data were obtained from the company's publicly available annual financial reports. The results of the analysis show a fluctuating trend in the company's profitability during the period, reflecting the impact of changing business strategies and market conditions. These findings provide insight for management in formulating more effective business strategies in the future.